2016
DOI: 10.2135/cropsci2015.05.0290
|View full text |Cite
|
Sign up to set email alerts
|

Development and Deployment of a Portable Field Phenotyping Platform

Abstract: Accurate and efficient phenotyping has become the biggest hurdle for evaluating large populations in plant breeding and genetics. Contrary to genotyping, high‐throughput approaches to field‐based phenotyping have not been realized and fully implemented. To address this bottleneck, a novel, low‐cost, flexible phenotyping platform, named Phenocart, was developed and tested on a field trial consisting of 10 historical and current elite wheat (Triticum aestivium L.) breeding lines at the International Maize and Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
60
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 42 publications
2
60
0
Order By: Relevance
“…However, our comparative GWAS demonstrated that, at least for plant height and stem diameter estimations at the end of the season, the genomic regions controlling these traits were coincident with those identified previously in studies that utilized the commercially used narrow row spacing. Our approach is an important technological breakthrough in high-throughput phenotyping because (1) Phenobot is auto-steered while other reported ground-based high-throughput phenotyping platforms must be operated by a driver (Montes et al, 2011;Comar et al, 2012;Barker et al, 2016); (2) our sensors (RGB stereo cameras) are inexpensive and readily available to researchers, although to date not frequently used in high-throughput phenotyping projects (Comar et al, 2012;Busemeyer et al, 2013;Crain et al, 2016); (3) stereo cameras were particularly selected to enable 3D plant reconstructions; (4) our lateral camera view facilitates the characterization of yield component traits such as stem diameter that cannot be estimated by aerial or top-view cameras; (5) our advances in feature extraction and algorithm development could be leveraged in other image-based phenotyping systems that employ alternative mobile platforms; and finally, (6) our platform that runs parallel to crop rows can be deployed to tall dense canopy crops such as sorghum, where high-clearance platforms (Andrade-Sanchez et al, 2014;Barker et al, 2016) could not be used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, our comparative GWAS demonstrated that, at least for plant height and stem diameter estimations at the end of the season, the genomic regions controlling these traits were coincident with those identified previously in studies that utilized the commercially used narrow row spacing. Our approach is an important technological breakthrough in high-throughput phenotyping because (1) Phenobot is auto-steered while other reported ground-based high-throughput phenotyping platforms must be operated by a driver (Montes et al, 2011;Comar et al, 2012;Barker et al, 2016); (2) our sensors (RGB stereo cameras) are inexpensive and readily available to researchers, although to date not frequently used in high-throughput phenotyping projects (Comar et al, 2012;Busemeyer et al, 2013;Crain et al, 2016); (3) stereo cameras were particularly selected to enable 3D plant reconstructions; (4) our lateral camera view facilitates the characterization of yield component traits such as stem diameter that cannot be estimated by aerial or top-view cameras; (5) our advances in feature extraction and algorithm development could be leveraged in other image-based phenotyping systems that employ alternative mobile platforms; and finally, (6) our platform that runs parallel to crop rows can be deployed to tall dense canopy crops such as sorghum, where high-clearance platforms (Andrade-Sanchez et al, 2014;Barker et al, 2016) could not be used.…”
Section: Discussionmentioning
confidence: 99%
“…A modified sprayer holding three types of sensors (infrared thermometers, sonar proximity sensor, and multispectral crop canopy sensor) was deployed in cotton fields to acquire plant height, normalized difference vegetation index (NDVI), and canopy temperature in differently irrigated conditions (Andrade-Sanchez et al, 2014) and to map QTLs for those traits (Pauli et al, 2016). A similar high-clearance vehicle with similar sensors was developed with a novel modular design, and its functionality was verified in wheat and soybean fields (Barker et al, 2016). A novel enclosed structure for controlled wind and lighting conditions was created to collect hyperspectral images of wheat genotypes to characterize and differentiate them using vegetation coverage and NDVI (Svensgaard et al, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The ground-based and unmanned aerial HTFP platforms that were developed for real-world phenotyping of above-ground traits include the following: (i) phenomobiles; (ii) pheno-fields; (iii) breedvision; (iv) phenocart; (v) pheno-towers; (vi) blimps; and (vii) infrared imagery (IR radiation sensor mounted on a light aircraft) [92][93][94][95]. However, the cost of HTFP platforms is rather high (cost $100,000 [96]), although recently, cheaper platforms such as "Phenocart" (cost $12,000) have also become available [97]. These platforms will be increasingly used in future for the phenotyping of traits that are relevant to drought tolerance [57].…”
Section: High Throughput Phenotypingmentioning
confidence: 99%
“…One strategy for improving and expediting the selection of these elite genotypes is the acquisition of high-dimensional phenotypic data (high-throughput phenotyping) (Bowman et al, 2015; Camargo and Lobos, 2016; Crain et al, 2016). …”
Section: Introductionmentioning
confidence: 99%